المصرف الصناعي العراقي ودوره في عملية التنمية الصناعية خلال المدة ( 1958 - 1963 ): دراسة تاريخية - الكندي، وفاء كاظم ماضي; السويدى، ميثم عبدالخضر جبار Alsuwaydi, Maytham Abdulkhedr Jabbar (جامعة بابل - كلية التربية للعلوم الإنسانية, 2018)
Before the Revolution of 14 July 1958, the Industrial Bank was linked administratively and organizationally with the Ministry of Economy. After the revolution, its organization was restructured and became linked to the Ministry of Industry. In order to promote industrial reality as the main engine of the various economic processes, Especially the construction of them, in order to upgrade and develop the infrastructure of the Iraqi economy was the direction of the Industrial Bank to support this sector, and this was clearly through the contribution of four companies specialized in the construction industries amounted to capital paid by (KD 2450) thousand, while the number of companies operating in the food industries companies amounted to capital paid (1050) thousand dinars followed by textile industries by two companies amounted to capital (2050) thousand dinars, and then leather industries, which were working in this area One with a capital of JD (190) thousand, but this arrangement does not show the reality of the situation correctly as the support and development not only through the number of companies, but the financial contribution ranked first in the calendar, and therefore the textile industries ranked first in the investment bank Industrial sector, with its contribution to this sector (41%) of the total contributions of the bank to the capital of the public sector industries. Since the beginning of 1960, the Industrial Bank has taken upon itself the task of developing the national industry by facilitating the development of these industries. The Board of Directors of the Bank, in its session held on 22 August 1960, outlined the bank's policy in the existing projects or the projects it intends to contribute or establish. The policy included the readiness of the Industrial Bank to contribute to existing or future projects, M material by the bank, provided that the condition of technical studies are available.
قبل قيام ثورة الرابع عشر من تموز 1958 كان المصرف الصناعي مرتبطاً من الناحية الإدارية والتنظيمية بوزارة الاقتصاد، وبعد ذلك أعيدت هيكلية تنظيمه وأصبح مرتبطاً بوزارة الصناعة، ومن أجل النهوض بالواقع الصناعي على اعتبار انه المحرك الرئيس لعمليات الاقتصاد المختلفة، عملت الحكومة العراقية على الاهتمام بقطع الصناعات التحويلية وخاصة الإنشائية منها وذلك من اجل ارتقاء وتطوير البنى التحتية للاقتصاد العراقي فكان توجه المصرف الصناعي بدعم هذا القطاع، وظهر ذلك بوضوح من خلال مساهمته بأربع شركات اختضت بالصناعات الإنشائية بلغت رؤوس أموالها المدفوعة بحدود (2450) ألف دينار، في حين بلغ عدد الشركات العاملة في الصناعات الغذائية شركات بلغت رؤوس أموالها المدفوعة (1050) ألف دينار تليها الصناعات النسيجية بواقع شركتين بلغت رؤوس أموالها (2050) ألف دينار، ثم الصناعات الجلدية والتي كانت تعمل في هذا المجال شركة واحدة بلغ رأس مالها بحدود (190) ألف دينار، إلا أن هذا الترتيب لا يظهر واقع الحال بصورة صحيحة إذ أن الدعم والتطوير ليس فقط من خلال عدد الشركات وإنما تحتل المساهمة المالية المركز الأول في التقويم، وعليه فان الصناعات النسيجية احتلت المرتبة الأولى في استثمارات المصرف الصناعي، إذ بلغت نسبة مساهمته في هذا الفرع من الصناعات بحدود (41%) من إجمالي مساهمات المصرف في رؤوس أموال صناعات القطاع العام، ومنذ مطلع عام 1960 أخذ المصرف الصناعي على عاتقه مهمة تنمية الصناعة الوطنية بتسهيل مهام تطويرها ودعمها بكل الوسائل المتوفرة لديه مادياً وفنياً ومعنوياً، ومن أجل تحقيق هذه الأهداف فقد أقرت إدارة مجلس المصرف بجلستها المنعقدة بتاريخ الثاني والعشرين/آب/1960 الخطوط العريضة لسياسة المصرف في المشاريع القائمة أو المشاريع التي ينوي المساهمة بها أو تأسيسها، وقد انطوت هذه السياسة على استعداد المصرف الصناعي في المساهمة في المشاريع القائمة أو التي تقام في المستقبل اذا كانت بحاجة إلى الدعم المادي من قبل المصرف شرط أن تتوفر فيها شرط الدراسات الفنية.
Keywords: المصرف الصناعي العراقي; الصناعات التحويلية; الصناعة; التنمية الصناعية